2017
DOI: 10.1177/0003489417709794
|View full text |Cite
|
Sign up to set email alerts
|

Smell and Taste Impairment After Total Laryngectomy

Abstract: Total laryngectomy determines olfactory and gustatory impairments that should be taken into account in clinical practice. Relationships between sensorial alterations, aging, follow-up period, and adjuvant treatments should be further evaluated in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The results of the olfactory threshold and identification tests and the time from laryngectomy to the start of rehabilitation were not correlated. Hiroto et al, 26 Miani et al, 27 and Riva et al 28 reported that the olfactory clefts, olfactory epithelia, and olfactory mucosa of laryngectomy patients with olfactory dysfunction were degenerated or atrophied. Karaoglu et al 29 reported greater nasal passage patency in the patient group (who underwent total laryngectomy more than 2 years previously) than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the olfactory threshold and identification tests and the time from laryngectomy to the start of rehabilitation were not correlated. Hiroto et al, 26 Miani et al, 27 and Riva et al 28 reported that the olfactory clefts, olfactory epithelia, and olfactory mucosa of laryngectomy patients with olfactory dysfunction were degenerated or atrophied. Karaoglu et al 29 reported greater nasal passage patency in the patient group (who underwent total laryngectomy more than 2 years previously) than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Such an aggressive approach improved both locoregional control and survival compared with RTX alone (38,39), but these flattering results were achieved at the price of significant functional morbidity. The inevitable sequelae of total laryngectomy include a permanent tracheostomy and the loss of natural voice; furthermore, patients are at risk of developing rare complications such as alterations in swallowing ability or olfactory changes due to loss of nasal airflow, as well as taste disorders, that often result in psychological disturbances and social embarrassment (40)(41)(42).…”
Section: Induction Chemotherapy and Laryngeal/hypopharyngeal Cancersmentioning
confidence: 99%
“…lost after trauma [16,18,19] or certain types of cancer [20][21][22][23]. Furthermore, the early olfactory deficit in AD [24] has been shown to be a strong predictor of the progression of dementia [25][26][27][28].…”
Section: Sensory Nervous Systemmentioning
confidence: 99%
“…The impairment in these senses can appear early in HNC patients and progressively become more severe in the long-term period [146]. Laryngeal cancer patients which are best treated by total laryngectomy, based on removal of the nasal neuroepithelium, suffer from hyposmia and gustatory alteration [21,147]. In normal conditions the olfactory receptors are not considered as potential contributors in cancerogenesis, but their physiological capability in binding to organic compounds and the subsequent signal transduction essential for survival or migratory events could support their involvement in fostering cancer cells [148][149][150].…”
Section: Cancermentioning
confidence: 99%